2016
DOI: 10.1007/s11103-016-0579-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of tomato membrane-bound NAC transcription factors

Abstract: Genome-wide analysis was carried out to identify and analyze differential expression pattern of tomato membrane bound NAC transcription factors (SlNACMTFs) during stresses. Two biotic-stress-related SlNACMTFs have been characterized to elucidate their regulatory function. NAC transcription factors are known regulators of stress-related gene expression. As Stresses are perceived and transmitted by membrane-bound proteins, functional characterization of membrane-associated NAC transcription factors in tomato can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 58 publications
3
32
0
Order By: Relevance
“…Membrane-bound transcription factors (MTF) are located in the membrane itself and are activated upon receiving of specific signal, and this regulation mode is considered to be accurate, such as membrane release [ 10 ]. Membrane-bound NAC transcription factors have been extensively identified and involved in many biological processes in different plant species [ 9 , 11 , 49 , 50 ]. In this study, we firstly identified 68 predicted membrane-bound NAC transcription factors in four cotton species and members are mainly distributed in the same subfamily, and these genes appear to be conserved during evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane-bound transcription factors (MTF) are located in the membrane itself and are activated upon receiving of specific signal, and this regulation mode is considered to be accurate, such as membrane release [ 10 ]. Membrane-bound NAC transcription factors have been extensively identified and involved in many biological processes in different plant species [ 9 , 11 , 49 , 50 ]. In this study, we firstly identified 68 predicted membrane-bound NAC transcription factors in four cotton species and members are mainly distributed in the same subfamily, and these genes appear to be conserved during evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Some NAC proteins have a transmembrane (TM) motif in the C-terminus, and show subcellular localization at the plasma membrane or endoplasmic reticulum; these proteins may be regulated by post-translational regulation under specific conditions [ 6 8 ]. Several species have membrane-bound NAC transcription factors, with 13 in Arabidopsis , 13 in tomato, 11 in soybean and 5 in rice, and most are induced by abiotic stresses [ 1 , 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we performed transient expression studies of the transcription factors in ¡316/C72 transgenic plant to appreciate their role in the promoter regulation. One of the tomato NAC proteins, SlNACMTF3 lacking the C-terminus domain, 23 slightly but significantly augmented the ¡316/C72 promoter activity ( Figure S8D). The predicted DREBbs has high level of homology with the similar CRT/DRE sites found in other stress-responsive genes (Fig.…”
Section: Dreb Protein Mediates Transcriptional Regulation Of Mir167a mentioning
confidence: 99%
“…The ABRE element has earlier been identified in the PSY promoter of Oryza sativa and Zea mays [ 26 , 27 , 28 ]. Besides, ABRE has been reported to play a crucial role in the regulation of NAC TFs under stressed condition [ 29 ]. The phytohormones play significant role in development and defense and hence presence of these elements in CsPSYp and CsUGTp point towards the possibility of their phytohormone mediated regulation.…”
Section: Discussionmentioning
confidence: 99%